Manajemen Dayah Inklusif: Pendidikan Alternatif bagi Anak Tunanetra Aceh - Almuhajir Almuhajir (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2020)
This study aims to describe the opportunities for the formation and initiation of the concept of inclusive Dayah management as an alternative education for Aceh blind children. Public education institutions in Aceh have facilitated the needs of many blind children, but Islamic-based educational institutions specifically do not yet have institutions that facilitate their needs. This research is a type of library research using an educational institution management approach. The results of the study showed that the Establishment of Inclusive Dayah was supported by the Aceh government policy system by establishing the Provincial and District/City Dayah Education Office, and enacting the Aceh Qanun Number 11 of 2014 on the Implementation of Aceh's Education and Law Number 20 of 2003 on the National Education System. Management of Inclusive Dayah for blind children can be carried out with the Special Inclusive Dayah Model, Visiting Class Inclusive Dayah, and Special Class Inclusive Dayah. Inclusive Dayah is an education service system that provides opportunities for school-age children with disabilities, especially children with visual impairment who are in the territory of Aceh Province by paying attention to diversity and individual needs. The potential of children with visual impairment can develop optimally in science along with the priority on Islamic religious education.